Controlled and Secure Sharing Threat Intelligence - Fernandes, Ricardo (2022)
Cyber threat information sharing platforms have become a useful weapon for dealing with cyberattacks, proactively mitigating them and thus reducing risk exposure. These allow multiple agencies to connect with each other, forming a community, and share that same intrusion information regarding cyberattacks or threats with each other. The Malware Information Sharing Platform (MISP) is particularly developed to promote the open dissemination of information such as intrusion indicators within a community. This exchange of information related to threats or incidents is treated as a data synchronisation procedure between di erent MISP instances, which may belong to one or more communities, companies or organisations. However, this platform presents limitations if its information is considered as classi ed or shared only for a certain period of time. This implies that this information should be treated only in encrypted form. One solution is to use MISP with searchable encryption techniques to impose greater control over information sharing. In this document, it is present a system that guarantees a controlled synchronisation of information between entities through the use of encrypted search techniques to guarantee the con dentiality of the information present in the MISP platform and also the use of synchronisation policies to control the way information is exchanged.